Association between angiotensin-converting enzyme gene polymorphism and coronary artery disease - (:unkn) unknown (My University, 1999)
An insertion/deletion (I/D) polymorphism in the gene for angiotensin- converting enzyme (ACE) is associated with myocardial infarction and other cardiac pathology. There is evidence for a role of the renin-angiotensin system in cell growth and in the repair of damaged arterial walls, so the ACE gene is postulated to be a candidate gene affecting the important clinical problem of coronary artery disease (CAD). In view of the clinical importance of the ACE as a major marker of cardiovascular diseases, we investigated the I/D polymorphism of the ACE gene in Turkish CAD patients in comparison with control subjects to evaluate a possible association between CAD and the gene encoding ACE. Polymerase chain reaction, restriction fragment length polymorphism, and agarose gel electrophoresis techniques were used to determine the ACE genotype in 58 subjects. The frequencies of ACE D and ACE I allele among the patients with CAD were 62.26% and 37.73% and in the control subjects were 49.3% and 50.76%, respectively. The greater frequency of deletion allele (D) was in the CAD group than in the control subjects was significant (P < 0.01).
Keywords: Angiotensin-converting enzyme gene polymorphism; Coronary artery disease